Comparative efficacy and safety of prophylactic norepinephrine and phenylephrine in spinal anesthesia for cesarean section: A systematic review and meta-analysis with trial sequential analysis - Peng Liu; Peng Liu; Hong He; Shan-Shan Zhang; Shan-Shan Zhang; Yun Liang; Yun Liang; Zi-Jun Gao; Hui Yuan; Bu-Huai Dong (Frontiers Media S.A., 2022)
Background: Phenylephrine is the first-line drug used to maintain blood pressure in cesarean delivery. However, it poses a high risk of bradycardia and depression of cardiac activity in pregnant women. Consequently, norepinephrine has gained popularity over the recent years, as an alternative to Phenylephrine because it is thought that prophylactic use of vasopressors may reduce the incidence of hypotension after spinal anesthesia. This systematic review compared the efficacy of both treatments.Methods: We searched the following databases; CNKI, PubMed, Embase, Web of science, clinicaltrials.gov, Medline and Cochrane Library, for randomized controlled trials comparing the prophylactic efficacy of norepinephrine and phenylephrine on elective cesarean delivery under spinal anesthesia. The search period was from inception to July 2022, and the primary outcome indicator was incidence of bradycardia. Statistical analysis was conducted on Rev manager 5.4, and the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) framework was used to evaluate the quality of evidence from each main finding.Results: A total of 12 papers were included in the analysis. The incidence of bradycardia (RR = 0.37, 95% CI: 0.28 to 0.49, p < 0.00001) and reactive hypertension (RR = 0.58, 95% CI 0.40 to 0.83, p = 0.003) was significantly lower in the norepinephrine (NE) group compared with the phenylephrine (PE) category. In contrast, there were no statistical differences in the umbilical cord blood gas analysis pH values between the groups (arterial: MD = 0.00, 95% CI −0.00 to 0.01, p = 0.22, vein: MD = 0.01, 95% CI −0.00 to 0.02, p = 0.06). The incidence of hypotension, nausea, and vomiting did not differ significantly between the NE and PE groups (hypotension: 23% vs. 18%; nausea: 14% vs. 18%; vomiting: 5% vs. 7%, respectively).Conclusion: Prophylactic use of norepinephrine is safe and effective in maintaining maternal hemodynamics without causing adverse events to either the pregnant woman or fetus.Systematic Review Registration: website https://www.crd.york.ac.uk/prospero/, identifier CRD42022347095